The local relevance of human rights - Feyter, K. de (Koen) (Cambridge : Cambridge University Press, 2011)
'Do human rights offer real protection when disadvantaged groups invoke them at the local level in an attempt to improve their living conditions? If so, how can we make sure that the experiences of those invoking human rights at the local level have an impact on the further development of human rights (at national and other levels) so that the local relevance of human rights increases? Since the adoption of the Universal Declaration of Human Rights (UDHR) on 10 December 1948, numerous international documents have reaffirmed human rights as global norms. This book examines what factors determine whether appeals to human rights that emanate from the local level are successful, and whether the UDHR adequately responds to threats as currently defined by relevant groups or whether a revision of some of the ideas included in the UDHR is needed in order to increase its contemporary relevance'--
Machine generated contents note: 1. Introduction: reconsidering human rights from below / Koen De Feyter and Stephan Parmentier; 2. Sites of rights resistance / Koen De Feyter; 3. Freedom from want revisited from a local perspective: evolution and challenges ahead Felipe Gomez Isa; 4. Relevance of human rights in the'glocal' space of politics: how to enlarge democratic practice beyond state boundaries and build up a peaceful world order? / Antonio Papisca; 5. The local relevance of human rights: a methodological approach / Gaby Ore Aguilar; 6. Ensuring compliance with decisions by international and regional human rights bodies: the case of the European Committee for the Prevention of Torture / Michelle Farrell; 7. Building rights-based health movements: lessons from the Peruvian experience / Alicia Ely Yamin and J. Jaime Miranda; 8. Defining human rights when economic interests are high: the case of the Western Shoshone / Julie Cavanaugh-Bill; 9. Struggling to localise human rights: the experience of indigenous peoples in Chile / Jose Aylwin; 10. Enforcing environmental rights under Nigeria's 1999 constitution: the localisation of human rights in the Niger Delta region / Rhuks Temitope Ako; 11. Conflict resolution through cultural rights and cultural wrongs: the Kosovo example / Maria del Mar Bermudez, Manuel Calzada Pla and Lydia Vicente Marquez; 12. Epilogue: widening the perspective on the local relevance of human rights / George Ulrich.
Includes bibliographical references and index.
Keywords: Human rights; Social justice; Globalization